Evidence-based Classification in Track Athletics for Athletes with a Vision Impairment: A Delphi Study. Issue 11 (November 2020) - Allen, Peter M.; Dolan, Rebecca; Croxall, Helen; Ravensbergen, Rianne H. J. C.; Brooks, Ashley; Zenk, Franziska; Mann, David L.
Abstract : SIGNIFICANCE: The Delphi analysis presented here highlights the need for a sport-specific evidence-based classification system for track athletics for athletes with a vision impairment (VI). This system may differ for different race distances. Further research is required to develop a useful test battery of vision tests for classification. The issue of intentional misrepresentation during classification needs particular attention. PURPOSE: At present, athletes with VI are placed into competition classes developed on the basis of legal definitions of VI. The International Paralympic Committee Athlete Classification Code states that all sports should have their own classification system designed to reflect the (visual) demands of that individual sport. This project gathered expert opinion on the specific requirements for an evidence-based sport-specific classification system for VI track athletics and to identify any particular issues within track athletics that require further research into their impact on sport performance. METHODS: A three-round Delphi review was conducted with a panel of 17 people with expertise in VI track athletics. RESULTS: The panel agreed that the current classification system in VI track athletics does not completely minimize the impact of impairment on competition outcome, highlighting the need for improvements. There was clear agreement that the existing measures of vision may fail to adequately reflect the type of vision loss that would impact running performance, with additional measures required. Intentional misrepresentation, where athletes "cheat" on classification tests, remains a serious concern. CONCLUSIONS: The panel has identified measures of vision and performance that will inform the development of an evidence-based classification system by better understanding the relationship between VI and performance in track athletics. Issues such as the use of guides and whether the current class system was equitable gave rise to differing opinions within the panel, with these varying across the different running distances. Abstract : Supplemental digital content is available in the text.